Avoiding cognitive biases: promoting good decision making in research methods courses. Issue 4 (19th May 2019) - Stapleton, Paul
ABSTRACT: The content of research methods courses in tertiary education, as revealed by popular textbooks, tends to focus largely on procedural aspects of research investigations. Although following proper procedures is essential for reaching valid and reliable outcomes, there is another attribute of good quality research that is often missing from research methods courses and textbooks: appropriate decision making and the avoidance of cognitive biases, such as confirmation bias and base rate neglect. In this essay, some of the more common cognitive biases are highlighted with examples from everyday life in order to illustrate how these biases can influence decision-making processes when reading about or conducting research investigations.